Cone Penetration Testing 2018 : Proceedings of the 4th International Symposium on Cone Penetration Testing (CPT'18), 21-22 June, 2018, Delft, The Netherlands - Michael A. Hicks; Federico Pisanò; Joek Peuchen (CRC Press, 2018)
Cone Penetration Testing 2018 contains the proceedings of the 4th International Symposium on Cone Penetration Testing (CPT'18, Delft, The Netherlands, 21-22 June 2018), and presents the latest developments relating to the use of cone penetration testing in geotechnical engineering. It focuses on the solution of geotechnical challenges using the cone penetration test (CPT), CPT add-on measurements and companion in-situ penetration tools (such as full flow and free fall penetrometers), with an emphasis on practical experience and application of research findings. The peer-reviewed papers have been authored by academics, researchers and practitioners from many countries worldwide and cover numerous important aspects, ranging from the development of innovative theoretical and numerical methods of interpretation, to real field applications. This is an Open Access ebook, and can be found on www.taylorfrancis.com.